Prognosis of patients with chronic myeloid leukemia presenting in advanced phase is defined mainly by blast count, but also by age, chromosomal aberrations and hemoglobin. Issue 11 (14th September 2019) - Lauseker, Michael; Bachl, Katharina; Turkina, Anna; Faber, Edgar; Prejzner, Witold; Olsson‐Strömberg, Ulla; Baccarani, Michele; Lomaia, Elza; Zackova, Daniela; Ossenkoppele, Gert; Griskevicius, Laimonas; Schubert‐Fritschle, Gabriele; et al.
Abstract: Chronic myeloid leukemia (CML) is usually diagnosed in chronic phase, yet there is a small percentage of patients that is diagnosed in accelerated phase or blast crisis. Due to this rarity, little is known about the prognosis of these patients. Our aim was to identify prognostic factors for this cohort. We identified 283 patients in the EUTOS population‐based and out‐study registries that were diagnosed in advanced phase. Nearly all patients were treated with tyrosine kinase inhibitors. Median survival in this heterogeneous cohort was 8.2 years. When comparing patients with more than 30% blasts to those with 20‐29% blasts, the hazard ratio (HR) was 1.32 (95%‐confidence interval (CI): [0.7‐2.6]). Patients with 20‐29% blasts had a significantly higher risk than patients with less than 20% blasts (HR: 2.24, 95%‐CI: [1.2‐4.0], P = .008). We found that the blast count was the most important prognostic factor; however, age, hemoglobin, basophils and other chromosomal aberrations should be considered as well. The ELTS score was able to define two groups (high risk vs non‐high risk) with an HR of 3.01 (95%‐CI: [1.81‐5.00], P < .001). Regarding the contrasting definitions of blast crisis, our data clearly supported the 20% cut‐off over the 30% cut‐off in this cohort. Based on our results, we conclude that a one‐phase rather than a two‐phase categorization of de novo advanced phase CML patients is appropriate.